EKSTRAKSI DAN PENGERINGAN POLISAKARIDA DARI JAMUR MERANG SAWIT VOLVARIELLA VOLVACEAE - Purwita, Rahmadina; Kusumaningtyas, Pintaka; Susanti, Revi; Anjarwati, Dewi; Febriyanti, Shinta; Romadhan G.F.F, Alfiqi Gilang Nur (PROSIDING SEMINAR KIMIA, 2024)
Polysaccharides are the main component in edible mushrooms and have an important role in food and medicine. Polysaccharide extraction methods and drying of mushroom simplicia are very important to obtain high polysaccharide soaks. The aim of this research was to determine the effect of adding pressure and alkali on the results of polysaccharide soaking extracted using the hot water extraction method, and the effect of different drying methods (food dehydrator and freeze drying) on the results of polysaccharide soaking. Stages in the research include: (1) collecting palm fungal biomass that grows on empty oil palm bunches, (2) preparing mushroom powder, (3) drying palm fungus biomass using a food dehydrator at a temperature of 70oC, (4) extracting dry palm fungus biomass using hot water, pressurized hot water and alkali, (5) determination of polysaccharide soak. The research results showed that the hot water extraction method without applying pressure gave a soaking yield of 3.85%, while with applying pressure the soaking yield was 8.29%. Re-extraction with the addition of alkaline solvent was able to increase the yield of polysaccharide soak by 5.08%. The research results also showed that the drying method influenced the results of the polysaccharide soak obtained. Drying with a food dehydrator was able to obtain higher soaking results (13.37%) compared to freeze drying (6.02%). Thus, it can be concluded that the oil palm mushroom simplicia which is dried with a food dehydrator and extracted using the hot water extraction method with pressure and alkali is able to increase the highest yield of polysaccharide soak. Keywords: hot water extraction, food dehydrator, freeze drying